Proceedings 16th International Parallel and Distributed Processing Symposium 2002
DOI: 10.1109/ipdps.2002.1015503
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and resolving remote memory access contention on hardware DSM multiprocessors

Abstract: This paper makes the following contributions: It proposes a new methodology for quantifying remote memory access contention on hardware DSM multiprocessors. The most valuable aspect of this methodology is that it assesses the impact of contention on real parallel programs running on real hardware. The methodology uses as input the number of accesses from each DSM node to each page in memory. A trace of the memory accesses of the program obtained at runtime from hardware counters is used to compute an accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Dynamic profiling works during the program execution, that is, it collects related information during the runtime. Mehofer and Scholz implemented a framework of probability data flows aiming at High Performance Fortran . The framework collects runtime control information, recognizes often executed paths and little executed paths, and then optimizes the communication.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic profiling works during the program execution, that is, it collects related information during the runtime. Mehofer and Scholz implemented a framework of probability data flows aiming at High Performance Fortran . The framework collects runtime control information, recognizes often executed paths and little executed paths, and then optimizes the communication.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments demonstrated that their optimization technologies improve the performance by 20.4%. Nikolopoulos presented a hardware‐supported dynamic page migration model, where a hardware counter keeps the access information of migrated pages to reduce the unnecessary page migration . Many international companies have also implemented a profiler in their products.…”
Section: Related Workmentioning
confidence: 99%
“…Contention accounts for an additional overhead of approximately 50 ns per contending node per access on the Origin2000 (37) and it has been shown that it can have a very significant impact on performance. (38) The behavior of the runtime data distribution algorithm is explained by classifying the benchmarks in two classes, coarse-grain and fine-grain benchmarks. In this context, granularity is associated with the duration of the parallel computation and the number of iterations that the program executes.…”
Section: Nas Benchmarksmentioning
confidence: 99%
“…Finally, the novelty in the work of Nikolopoulos [34] is the fact that it deals with the remote memory access issue. This paper presents a methodology for quantifying remote memory access contention on hardware cache-coherent DSM multiprocessors.…”
Section: Proposals On Memory System Aware Schedulingmentioning
confidence: 99%